Using System Dynamics Computer Modeling Software to Teach Cause-Effect Relationships in Reading Selections - Eckleberry, Virgil Vernon (My University, 2001)
The purpose of this study was to determine if the use of system dynamics computer modeling software would affect student ability to recognize cause-effect relationships in reading selections. Pre- and posttests were administered to measure changes in reading comprehension and a pre- and post-intervention Likert Scale survey was administered to determine changes in student attitudes relating to the use of computer software in reading instruction. A performance rubric was also used to gauge progress specifically related to using system dynamics computer modeling techniques for identifying cause-effect relationships in reading selections. The setting was an inner city gifted center and the participants were fourth and fifth- graders who attend the center one day per week. System dynamics strategies were used to examine reading selections and, as the culminating activity, STELLA computer modeling software was used to model diagrams of the causal relationships within stories. Because of the one- group pretestposttest design, no conclusive results could be obtained, however, it was concluded, based on observations and data, that the ability of students to recognize cause-effect relationships in selected readings improved as a result of the intervention.
Keywords: system dynamics; computer modeling software; cause-effect relationships; STELLA